1985
DOI: 10.1002/jsfa.2740360105
|View full text |Cite
|
Sign up to set email alerts
|

The effect of straw incorporation on the uptake of nitrogen by winter wheat

Abstract: There was a small decrease in grain yield (from 10.8 to 10.5 t ha-') when wheat straw (3 t dry matter ha-') was incorporated into a silty clay loam soil sown to winter wheat. In the absence of straw, 60% of autumn-applied '5N-labelled nitrate was lost from the crop:soil system. Straw incorporation decreased this loss to 47%. There was little overall effect on the uptake of N by the crop, presumably because straw immobilised inorganic N that would otherwise have been leached from the soil during winter. Only 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 4 publications
7
30
0
2
Order By: Relevance
“…We attribute the greater N availability of below-ground residues, especially that of pea, partly to their higher mineralizability resulting from lower C:N ratio of root compared to straw. The small contribution of straw residues to the subsequent crop N uptake is consistent with most findings in the literature (1 to 5% range for cereals and pulse crop residues as reported by Powlson et al 1985;Bremer and van Kessel 1992;Jensen 1994Jensen , 1996a, and suggests that removal of straw has little effect on plant N nutrition in the short term. The barley following pea also appeared to derive more of its N from the soil than the canola following barley.…”
Section: Crop Nitrogen Uptake Partitioningsupporting
confidence: 90%
See 1 more Smart Citation
“…We attribute the greater N availability of below-ground residues, especially that of pea, partly to their higher mineralizability resulting from lower C:N ratio of root compared to straw. The small contribution of straw residues to the subsequent crop N uptake is consistent with most findings in the literature (1 to 5% range for cereals and pulse crop residues as reported by Powlson et al 1985;Bremer and van Kessel 1992;Jensen 1994Jensen , 1996a, and suggests that removal of straw has little effect on plant N nutrition in the short term. The barley following pea also appeared to derive more of its N from the soil than the canola following barley.…”
Section: Crop Nitrogen Uptake Partitioningsupporting
confidence: 90%
“…Bremer and van Kessel (1992) reported that about 6% of mature lentil (Lens culinaris Medikus) and wheat straw N was assimilated by the following spring-sown crop. Others (Powlson et al 1985;Jensen 1994Jensen , 1996a found that 8 to 15% of pea and cereal straw N was recovered by the subsequent autumn-sown crops.…”
Section: Crop Nitrogen Uptake Partitioningmentioning
confidence: 99%
“…Soil mineral N content was significantly (P < 0.05) lower in PSBS than in PS plots at days 3 and 7. These results indicate that part of the soil N was immobilised following straw addition, as previously reported (Powlson et al 1985;Ocio et al 1991). The maximum N immobilisation occurred in PSBS at day 3 and represented 36% of slurry NH 4 -N added to the soil.…”
Section: Nitrogen Transformationssupporting
confidence: 87%
“…Soil nitrogen is consumed by the microorganisms involved in this process, and very little nitrogen is leached into the tile drainage, unless more precipitation occurs (Romanovskaja and Tripolskaja, 2003). Nitrogen leaching decreased by 47% when 3 t ha -1 of dry material was added to the soil (Powlson et al, 1985). However, degradation of the straw increases the amount of mobile phosphorus in the soil (Jenkyn et al, 2001).…”
Section: Effects Of Additives In Trench Backfillsmentioning
confidence: 99%